Advances in the understanding of Mycobacterium tuberculosis transmission in HIV-endemic settings. Issue 3 (March 2019) - Peters, Julian S; Andrews, Jason R; Hatherill, Mark; Hermans, Sabine; Martinez, Leonardo; Schurr, Erwin; van der Heijden, Yuri; Wood, Robin; Rustomjee, Roxana; Kana, Bavesh D
Summary: Tuberculosis claims more human lives than any other infectious disease. This alarming epidemic has fuelled the development of novel antimicrobials and diagnostics. However, public health interventions that interrupt transmission have been slow to emerge, particularly in HIV-endemic settings. Transmission of tuberculosis is complex, involving various environmental, bacteriological, and host factors, among which concomitant HIV infection is important. Preventing person-to-person spread is central to halting the epidemic and, consequently, tuberculosis transmission is now being studied with renewed interest. In this Series paper, we review recent advances in the understanding of tuberculosis transmission, from the view of source-case infectiousness, inherent susceptibility of exposed individuals, appending tools for predicting risk of disease progression, the biophysical nature of the contagion, and the environments in which transmission occurs and is sustained in populations. We focus specifically on how HIV infection affects these features with a view to describing novel transmission blocking strategies in HIV-endemic settings.